Advances in positive organizational psychology. Vol. 1 - Bakker, Arnold B. (Emerald, 2013)
This volume attempts to build a bridge between POB and Positive Organizational Scholarship (POS). Similar to POB, but different from positive psychology, the primary emphasis of POS is on the workplace and on the accomplishment of work-related outcomes. The volume includes contributions from both fields, and theories and studies in which a positive individual perspective (POB) is combined with a positive organization perspective (POS).
Includes indexes.
Keywords: Organizational behavior.; Psychology, Industrial.; Organizational learning.; Organizational effectiveness.; elektronické knihy; electronic books